2024
DOI: 10.1186/s42358-024-00351-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interleukin-17 family cytokines in disease severity of patients with knee osteoarthritis

Zahra Kamiab,
Hossein Khorramdelazad,
Mehdi Kafi
et al.

Abstract: Background Interleukin-17 (IL-17) family plays a role in the pathogenesis of knee osteoarthritis (KOA) by contributing to the inflammatory and destructive processes in the affected joint. This study aimed to measure levels of IL-17 A and IL-25 (IL-17E) in serum of KOA patients and determine their roles in the disease severity of patients. Methods In this, 34 patients with KOA and 30 age and sex-matched healthy subjects (HS) were enrolled. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Treatment strategies involve symptom management, lifestyle modifications, physical therapy, and, in severe cases, surgical interventions based on medical histories and physical examinations ( 4 6 ). Evidence revealed that the immune system and its components play a pivotal role in the pathogenesis of OA because immune cells are activated in OA, contributing to cartilage degradation and joint inflammation ( 7 , 8 ). Inflammatory mediators are released in OA, contributing to cartilage degradation and joint inflammation, previously considered a non-inflammatory disease ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment strategies involve symptom management, lifestyle modifications, physical therapy, and, in severe cases, surgical interventions based on medical histories and physical examinations ( 4 6 ). Evidence revealed that the immune system and its components play a pivotal role in the pathogenesis of OA because immune cells are activated in OA, contributing to cartilage degradation and joint inflammation ( 7 , 8 ). Inflammatory mediators are released in OA, contributing to cartilage degradation and joint inflammation, previously considered a non-inflammatory disease ( 9 ).…”
Section: Introductionmentioning
confidence: 99%